Advancing green bond pricing in India: A theory-driven framework integrating certification, disclosure and market liquidity - Karri Manikanteswara Reddy; Ch Srinivas; P Uma Maheswari Devi (Studies in Economy and Public Policy, 2026)
Purpose: This study develops a structured framework to explain how certification, disclosure, liquidity, regulatory incentives, and issuer credibility influence green bond pricing in India. It integrates theory and market evidence to clarify how these determinants shape investor behavior and pricing outcomes. Methodology: A conceptual research design is used, drawing on signalling, information asymmetry, and market microstructure theories. This study reviews international literature, SEBI and RBI regulations, and market practices to construct an integrated pricing framework and nine propositions for empirical validation. Results: The analysis shows that credible certification, strong disclosure, deeper liquidity, digital transparency tools, and supportive regulatory measures reduce information gaps, strengthen environmental credibility, and enhance pricing efficiency. These mechanisms lower yield spreads, increase investor participation, and expand financing for climate-aligned infrastructure. Conclusions: This study highlights that certification quality, disclosure practices, liquidity, regulatory support, and issuer credibility influence green bond pricing in India. Stronger reporting standards and regulatory reforms can improve transparency and investor confidence. Limitations: The framework is conceptual and requires validation using panel data on sovereign, corporate, and municipal green bonds in India. Contributions: This study introduces a unified, theory-driven pricing model tailored to India’s regulatory and institutional context and offers nine testable propositions to guide future empirical research. Novelty: This study provides one of the first integrated models linking certification, disclosure, liquidity, and regulatory incentives to pricing outcomes in India, offering a structured roadmap for empirical testing and policy design.